Three-dimensional torso motion in tethered front crawl stroke and its implications on low back pain - Du, T.; Narita, T.; Yanai, T. (Journal of Applied Biomechanics, 2016)
Low back pain is a common problem among competitive swimmers, and repeated torso hyperextension is claimed to be an etiological factor. The purpose of this study was to describe the three-dimensional torso configurations in the front crawl stroke and to test the hypothesis that swimmers experience torso hyperextension consistently across the stroke cycles. Nineteen collegiate swimmers underwent 2 measurements: a measurement of the active range of motion in 3 dimensions and a measurement of tethered front crawl stroke at their maximal effort. Torso extension beyond the active range of torso motion was defined as torso hyperextension. The largest torso extension angle exhibited during the stroke cycles was 9 ± 11° and it was recorded at or around 0.02 ± 0.08 s, the instant at which the torso attained the largest twist angle. No participant hyperextended the torso consistently across the stroke cycles and subjects exhibited torso extension angles during tethered front crawl swimming that were much less than their active range of motion. Therefore, our hypothesis was rejected, and the data suggest that repeated torso hyperextension during front crawl strokes should not be claimed to be the major cause of the high incidence of low back pain in swimmers.